1994
DOI: 10.1111/j.1365-2605.1994.tb01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the dog epididymis: a model for human epididymal function

Abstract: The physiology of the epididymis is an integral part of the maturation process by which human spermatozoa acquire the ability to reach and fertilize an oocyte. Because of the high degree of species specificity exhibited by the epididymal proteins involved in sperm maturation, we have assessed tissue from several alternative species for their suitability as a model for human epididymal physiology. Of these, the dog appears to offer an appropriate system. Northern hybridization using cDNA probes specific for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
(29 reference statements)
1
26
0
Order By: Relevance
“…Previous studies have shown the existence of HE4 homologues in rabbit (BE-20, U26725) (Xu et al, 1996) and dog (CE4, S77395) (Ellerbrock et al, 1994). By searching the public EST databases we were able to identify further homologues from pig (represented by BE234395), mouse (AF334269) and rat (represented by AI411527).…”
mentioning
confidence: 94%
“…Previous studies have shown the existence of HE4 homologues in rabbit (BE-20, U26725) (Xu et al, 1996) and dog (CE4, S77395) (Ellerbrock et al, 1994). By searching the public EST databases we were able to identify further homologues from pig (represented by BE234395), mouse (AF334269) and rat (represented by AI411527).…”
mentioning
confidence: 94%
“…Proteins with an identical peptide backbone have been isolated from various primates (Perry et al, 1995;Fröhlich and Young, 1996), and represent approximately 20% of the luminal protein content of cauda epididymidal fluid in chimpanzees (Fröhlich and Young, 1996). Closely related products have been identified in non-primate species (Ellerbrock et al, 1994;Syntin et al, 1996). However, the HE1 peptide sequence seems evolutionarily to be much older; a similar protein (esr16; accession no.…”
Section: Putative Cholesterol Carriersmentioning
confidence: 99%
“…Closely related proteins have been cloned from epididymal tissue of other species (Ellerbrock et al, 1994;Xu et al, 1996). The positions of half-cysteines suggested that they are twodomain members of the 'four-disulfide core'-or 'whey acidic' protein (WAP)-domain proteins, to which the human seminal plasma proteinase inhibitor, HUSI-I/SLPI (Seemüller et al, 1986;Jin et al, 1997), and a decapacitation factor of guinea-pig spermatozoa, caltrin II, belong (Coronel and Lardy, 1992).…”
Section: Putative Secretory Proteinase Inhibitorsmentioning
confidence: 99%
“…Its secretion varies with different phases of lactation (44), and it possibly plays a role in hair and nail growth (45). Although the physiological functions of epididymal proteins such as HE4, CE4, and BE20 (30,46,47) in the male genital tract are not clear, they may act as decapitation factors that bind to sperm that are released in the female reproductive tract (48).…”
Section: Discussionmentioning
confidence: 99%